Subjects of transportation processes and their relationships - Cempírek, Václav; Kampf, Rudolf (Univerzita Pardubice, 2006)
This article was created as a part of researched grant project (GA ČR) „Transportation - logistical processes outsourcing“ on the Jan Perner Transport Faculty, University of Pardubice. The subjects are described in this article that are related to problem of selection of the form of transport as a part of transportation processes (customers, transport operators, forwarders, state (society) and relationships between the participants of transportation processes. Two basic models of selection of form of transport (Classic economical model and Model of total logistic costs ) are described in the next part of this article.
Subjekty dopravních a přepravních procesů a jejich vzájemné vztahy
Keywords: dopravní procesy; přepravní procesy; výběr druhu dopravy; zákazníci; dopravci; zasilatelé